Seizure freedom improves health‐related quality of life after epilepsy surgery in children. (11th November 2019) - Jain, Puneet; Smith, Mary Lou; Speechley, Kathy; Ferro, Mark; Connolly, Mary; Ramachandrannair, Rajesh; Almubarak, Salah; Andrade, Andrea; Widjaja, Elysa; ,
Abstract : Aim: To determine whether epilepsy surgery improved health‐related quality of life (HRQoL) and whether seizure freedom after surgery mediated the improvement in HRQoL. Method: This multicenter cohort study compared HRQoL after epilepsy surgery to pharmacological management in children with drug‐resistant epilepsy (DRE). HRQoL was measured using the Quality of Life in Childhood Epilepsy (QOLCE) questionnaire at baseline and 1‐year follow‐up. The mediator between treatment type and HRQoL was seizure freedom. Results: Two hundred and thirty‐seven patients were recruited (surgery group: n =147 [92 males, 45 females]; pharmacological group: n =90 [53 males, 37 females]). Mean age at seizure onset was 6 years (SD 4y 4mo) in the surgical group and 6 years 1 month (SD 4y) in the pharmacological group. The odds ratio of seizure freedom was higher for the surgery versus pharmacological group (β=4.24 [95% confidence interval CI: 2.26–7.93], p <0.001). Surgery had no direct effect on total QOLCE score at 1‐year (β=0.24 [95% CI –2.04 to 2.51], p =0.839) compared to pharmacological management, but had an indirect effect on total QOLCE that was mediated by seizure freedom (β=0.92 [95% CI 0.19–1.65], p =0.013), adjusting for baseline total QOLCE score. Surgery had a direct effect on improving social function ( p =0.043), and an indirect effect on improving physical function ( p =0.016), cognition ( p =0.042), social function ( p =0.012) and behavior ( p =0.032), mediated by seizure freedom. Interpretation: Greater seizure freedom achieved through epilepsy surgery mediated the improvement in HRQoL compared to pharmacological management in children with DRE. What this paper adds: Seizure freedom is higher after pediatric epilepsy surgery compared to pharmacologically managed epilepsy. Surgery indirectly improves health‐related quality of life (HRQoL) mediated by seizure freedom compared to pharmacological management. Surgery has a direct effect on improving social function relative to pharmacological management. Baseline HRQoL was an important predictor of HRQoL after treatment. What this paper adds: Seizure freedom is higher after pediatric epilepsy surgery compared to pharmacologically managed epilepsy. Surgery indirectly improves health‐related quality of life (HRQoL) mediated by seizure freedom compared to pharmacological management. Surgery has a direct effect on improving social function relative to pharmacological management. Baseline HRQoL was an important predictor of HRQoL after treatment. This article's abstract has been translated into Spanish and Portuguese. Follow the links from the abstract to view the translations. This article is commented on by Varadkar on pages 544–545 of this issue. Resumen: La ausencia de crises epilépticas en niños mejora la calidad de vida relacionada con la salud después de la cirugía de epilepsia: Objetivo: Determinar si la cirugía de epilepsia mejora la calidad de vida relacionada con la salud (HRQoL) y si la ausencia de crises epilépticas después de la cirugía intervino en la mejora. Metodo: Estudio de cohorte, multicéntrico que evaluó la HRQoL después de la cirugía de epilepsia comparándolo con el manejo farmacológico, en niños con epilepsia farmacorresistente (DRE). La HRQoL se midió utilizando el cuestionario de calidad de vida en la infancia (QOLCE) al inicio y después de un año de seguimiento. El mediador entre el tipo de tratamiento y HRQoL fue la ausencia de crises epilépticas. Resultados: Se reclutaron 237 pacientes (grupo de cirugía: n 147 [92 varones, 45 mujeres]; grupo farmacológico: n 90 [53 varones, 37 mujeres]). La edad promedio al inicio de las crisis epilépticas fue de 6 años (DE 4 años 4 meses) en el grupo quirúrgico y 6 años 1 mes (DE 4 años) en el grupo farmacológico. La relación de probabilidad de la ausencia de crises epilépticas fue mayor para el grupo de cirugía frente a farmacológico (β = 4, 24 [intervalo de confianza (IC) 95 %: 2.26–7.93], p <0.001). La cirugía no tiene ningún efecto directo sobre la puntuación total de QOLCE a 1 año (β = 0, 24 [IC del 95% –2, 04 a 2, 51], p =0, 839) en comparación con el tratamiento farmacológico, pero tiene un efecto indirecto en el QOLCE total que fue mediado por la ausencia de crises epilépticas (β = 0, 92 [IC del 95% 0, 19–1, 65], p= 0, 013), ajustando la puntuación total de QOLCE. La cirugía tuvo un efecto directo en la mejora de la función social (p =0.043), y un efecto indirecto en la mejora de la función física (p=0.016), la cognición ( p =0, 042), la función social (p=0.012) y el comportamiento (p=0.032), mediado por la ausencia de crises epilépticas. Interpretacion: En este estudio encontramos que en niños con DRE la ausencia mas significativa de crises epilépticas, lograda a través de la cirugía de epilepsia, mediaba una mejor HRQoL en comparación con el manejo farmacológico. Resumo: Ficar sem crises epilépticas melhora a qualidade de vida relacionada à saúde após cirurgia para epilepsia em crianças: Objetivo: Determinar se a cirurgia para epilepsia melhora a qualidade de vida relacionada à saude (QVRS) e se ficar sem crises epilépticas após a cirurgia media a melhora na QVRS. Método: Este estudo de coorte multicêntrico comparou a QVRS após cirurgia para epilepsia ao manejo farmacológico em criancas com epilepsia resistente a drogas (ERD). A QVRS foi medida usando o questionário Qualidade de Vida na Epilepsia Infantil (QVEI) na linha de base e no acompanhamento após 1 ano. O mediador entre o tipo de tratamento e a QVRS foi estar sem crises epilépticas. Resultados: Duzentos e trinta e sete pacientes foram recrutados (grupo cirurgia: n =147 [92 do sexo masculino, 45 do sexo feminino]; grupo farmacológico: n =90 [53 do sexo masculino, 37 do sexo feminino]). A média de idade no início das crises foi 6 anos (DP 4a 4m) no grupo cirúrgico e 6 anos e 1 mês (DP 4a) no grupo farmacológico. A taxa de risco de estar sem crises foi maior no grupo cirurgia versus farmacológico (β=4, 24 [intervalo de confiança a 95% IC: 2, 26–7, 93], p <0, 001). A cirurgia não teve efeito direto no QVEI total após 1 ano (β=0, 24 [IC 95% –2, 04 a 2, 51], p =0, 839) comparada ao manejo farmacológico, mas teve efeito indireto no QVEI total que foi medido pelo fato de estar livre de crises (β=0, 92 [IC 95% 0, 19–1, 65], p =0, 013), ajustando para o escore total QVEI na linha de base. A cirurgia teve efeito direto na melhora da função social ( p =0, 043), e efeito indireto na melhora da função física ( p =0, 016), cognição ( p =0, 042), função social ( p =0.012) comportamento ( p =0, 032), mediada pelo fato de estar sem crises. Interpretação: A maior chance de ficar sem crises, atingida por meio da cirurgia, mediou a melhora na QVRS em comparação com o manejo farmacológico em crianças com ERD.